2023
DOI: 10.2196/41762
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Purchase of Over-the-Counter Medications and Ovarian Cancer Diagnosis in the Cancer Loyalty Card Study (CLOCS): Observational Case-Control Study

Abstract: Background Over-the-counter (OTC) medications are frequently used to self-care for nonspecific ovarian cancer symptoms prior to diagnosis. Monitoring such purchases may provide an opportunity for earlier diagnosis. Objective The aim of the Cancer Loyalty Card Study (CLOCS) was to investigate purchases of OTC pain and indigestion medications prior to ovarian cancer diagnosis in women with and without ovarian cancer in the United Kingdom using loyalty car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…As noted earlier, there are numerous examples, including mobile telephone data, social media posts, credit card use, loyalty card use and wearable device data. The recent CLOCS study 34 , evaluated loyalty card purchases within two retailers in 153 women with OC, compared to healthy controls, to determine if shopping habits could be used as proxy symptoms indicators and facilitate the detection of disease. Whilst an association between OC and purchases of over-the-counter indigestion (AUC 0.65) and pain (AUC 0.63) medications was identified, the results must be interpreted with an element of caution, given the control group consisted of healthy population rather than symptomatic women with a benign condition.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, there are numerous examples, including mobile telephone data, social media posts, credit card use, loyalty card use and wearable device data. The recent CLOCS study 34 , evaluated loyalty card purchases within two retailers in 153 women with OC, compared to healthy controls, to determine if shopping habits could be used as proxy symptoms indicators and facilitate the detection of disease. Whilst an association between OC and purchases of over-the-counter indigestion (AUC 0.65) and pain (AUC 0.63) medications was identified, the results must be interpreted with an element of caution, given the control group consisted of healthy population rather than symptomatic women with a benign condition.…”
Section: Discussionmentioning
confidence: 99%
“…The aims, design and results of CLOCS have previously been reported 9 10. CLOCS is an observational case–control study where participants are women in the UK, aged 18 years or older, who hold a loyalty card at either or both participating high street retailers (HSR1 and HSR2).…”
Section: Methodsmentioning
confidence: 99%
“…The Cancer Loyalty Card Study (CLOCS) investigated the period between the presentation of the first symptom(s)/sign(s) leading up to the first presentation at healthcare providers (ie, the patient interval) of patients with ovarian cancer to better understand self-care behaviours using past purchase information collected through loyalty cards at two high street retailers in the UK 9. This project aimed to better understand whether self-care behaviours can be detected at an early stage and facilitate earlier presentation to healthcare providers, and the main results have been reported elsewhere 10. We have previously reported in a proof-of-concept study that loyalty card data may be used to identify an increase in painkiller and indigestion medication purchases among patients with ovarian cancer 11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from loyalty cards used in over-the-counter purchases of medicines could be used to help diagnose ovarian cancer cases earlier, a study published in JMIR Public Health and Surveillance has suggested 1…”
mentioning
confidence: 99%